Integrating a Love-Based Curriculum and Pedagogical Deep Learning for Character Transformation in Indonesian Islamic Senior High Schools - Guntur Cahaya Kesuma; Muhammad Aridan; Mohammed H. Al Aqad; Umi Hijriyah (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
The rapid growth of digital technology has intensified moral challenges in Islamic education, including bullying, cyberbullying, and declining reflective and ethical reasoning among students. Although previous studies have established relationships between religiosity, character education, and student behavior, they have largely remained correlational or conceptual, providing limited evidence on how value-based curricula can be pedagogically operationalized to achieve observable character transformation. This study analyzes the integration of the Love-Based Curriculum (KBC) and deep learning in Islamic Religious Education (PAI) to foster character transformation among Madrasah Aliyah students. A qualitative multi-case study was conducted across three Madrasah Aliyah using participatory observations, semi-structured interviews, and curriculum document analysis. The findings indicate that integrating KBC values through deep learning pedagogies positively transformed the school climate by increasing student engagement, reflective understanding of religious teachings, and meaningful participation in collaborative learning. The study also documented substantial reductions in bullying behaviors alongside increased student social participation and empathy. These changes were associated with the alignment of compassion-based curriculum values and deep learning strategies that promote critical reflection, ethical dialogue, contextual problem-solving, and prosocial behavior. The study contributes theoretically by demonstrating how value-based education can be operationalized through deep learning pedagogy, providing empirical evidence of value internalization and proposing an integrative model explaining the relationship between pedagogical processes and character transformation. The findings further highlight that the successful implementation of the Love-Based Curriculum depends not only on curriculum policy but also on teacher readiness and sustained institutional support for reflective and dialogical learning.